Developing New PVT Correlations for Libyan Crude Oil Using Samples from Different Reservoirs - Burgan, Taha A.; Moammer, Saleh F.; Aghanaya, Mahfoud Z.; Khair, Ali A. (The Indonesian Institute of Science and Technology Research, 2024)
Five PVT correlations including bubble point pressure, solution gas-oil ratio, oil formation volume factor, dead oil viscosity, and oil density were used to analyze a total of 102 data sets from the Libyan crude oil reservoirs representing Sirte, Ghdames, Murzug, and offshore Tripolitania basins, to find a new more accurate correlation. Linear & nonlinear regression and statistical software packages (Excel, Minitab, and Mat lab software) were applied to the above-mentioned crude samples. The application of multilinear regression and statically software on the solution gas, oil ratio, temperature, and API gravity, exhibit a direct proportionality with the bubble point, whereas in the case of gas gravity, the correlation shows inversely proportionality with the bubble point. The relationships between the solution gas oil and other properties show that the distribution of the tested points in these investigations are located very close to the 45° trend line fourth solution gas oil ratio, indicating that the correlations have higher accuracy with our newly developed PVT equations for the analyzed Libyan crude oil samples. The cross plots between measured vs. calculated oil formation factor, dead oil viscosity, and oil density play a very good reliable correlation compared with previously published correlations done by other researchers as well as in the statistical calculation, in addition, the AARE and R2 results were calculated for previous published correlation in different locations over the world. Based on the obtained results in this research, the proposed correlations are more accurate than all the other previously published correlations, exclusively for Libyan crude oil.